Arginine supplementation reduces colonic injury, inflammation and oxidative stress of DSS-induced colitis in mice. (January 2019) - Andrade, Maria Emília Rabelo; Barros, Patrícia Aparecida Vieira de; Menta, Penélope Lacrísio dos Reis; Costa, Grazielle Mara Ferreira; Miranda, Sued Eustáquio Mendes; Leocádio, Paola Caroline Lacerda; Almeida-Leite, Camila Megale de; Generoso, Simone de Vasconcelos; Leite, Jacqueline Isaura Alvarez; Cardoso, Valbert Nascimento
Graphical abstract: Highlights: Arginine supplementation reduced inflammation and lipid peroxidation. Arginine supplementation preserved mucosal architecture and reduced IP and BT. Treatment with arginine modulated immune response. Arginine treatment increased collagen production and reduced iNOS mRNA expression. Abstract: This study evaluated the mechanisms action of arginine in experimental model of ulcerative colitis. C57BL/6 mice were randomized into 4 groups: Control group (C): standard diet; Colitis group (Col): standard diet and DSS solution; Pretreated group (PT): diet supplementation with arginine before and during colitis induction; Treated group (T): diet supplementation with arginine during colitis induction. Colitis was induced by administration of 1.5% DSS for 5 days. Parameters such as intestinal permeability (IP), bacterial translocation (BT), histological and morphometric analysis, cytokines, immunoglobulin A, inflammatory infiltrate, oxidative stress, tight junction, iNOS 1 were performed. The Col group showed increased IP, BT, oxidative stress and inflammatory infiltrate in the colon. Arginine decreased IP, BT, oxidative stress and inflammatory infiltrate in the colon. Only, the group T reduced iNOS, cytokine IL-17, 2 and increased collagen area and cytokine TGF-β. 3 These results suggest that arginine can constitute in potential therapy for colitis.